Recent advances in PGPR-mediated resilience toward interactive effects of drought and salt stress in plants - Al-Turki, Ahmad; Murali, M.; Omar, Ayman F.; Rehan, Medhat; Sayyed, R.Z. (Frontiers in Microbiology, 2023)
The present crisis at hand revolves around the need to enhance plant resilience to various environmental stresses, including abiotic and biotic stresses, to ensure sustainable agriculture and mitigate the impact of climate change on crop production. One such promising approach is the utilization of plant growth-promoting rhizobacteria (PGPR) to mediate plant resilience to these stresses. Plants are constantly exposed to various stress factors, such as drought, salinity, pathogens, and nutrient deficiencies, which can significantly reduce crop yield and quality. The PGPR are beneficial microbes that reside in the rhizosphere of plants and have been shown to positively influence plant growth and stress tolerance through various mechanisms, including nutrient solubilization, phytohormone production, and induction of systemic resistance. The review comprehensively examines the various mechanisms through which PGPR promotes plant resilience, including nutrient acquisition, hormonal regulation, and defense induction, focusing on recent research findings. The advancements made in the field of PGPR-mediated resilience through multi-omics approaches (viz., genomics, transcriptomics, proteomics, and metabolomics) to unravel the intricate interactions between PGPR and plants have been discussed including their molecular pathways involved in stress tolerance. Besides, the review also emphasizes the importance of continued research and implementation of PGPR-based strategies to address the pressing challenges facing global food security including commercialization of PGPR-based bio-formulations for sustainable agricultural.